Perancangan Sistem Informasi Penyewaan Gedung PGRI Ciruas Berbasis Web Menggunakan Framework Laravel - Adilla Salma; Gagah Dwiki Putra Aryono; Maman Masyhuri (JURNAL MANAJEMEN PENDIDIKAN, 2025)
DESIGN OF A WEB-BASED HALL RENTAL INFORMATION SYSTEM FOR PGRI CIRUAS USING LARAVEL FRAMEWORK The manual rental process of the PGRI Ciruas Hall has caused several problems, including limited access to information, uncentralized data, delayed confirmations and inefficient transaction handling. This study aimed to design and develop a web-based information system to streamline and enhance the hall rental process. The system was developed using the Waterfall method, involving stages such as needs analysis, literature study, system design, implementation and testing. It was built using the Laravel framework and supports user registration with email verification, login, online booking, multiple payment methods, facility selection, Google Maps location, rental history and WhatsApp chat support. On the admin side, it features rental data management, facility control, payment verification (automated and manual), and downloadable reports in PDF or Excel format. Black-box testing showed that the system operated as expected in both user and admin modules. The results indicate that this system improves rental service efficiency, ensures accurate data management and provides a user-friendly platform accessible anytime and anywhere.